The invention of lying [videorecording (DVD)] - Gervais, Ricky; Gervais, Ricky; Robinson, Matthew, 1978-; Robinson, Matthew, 1978-; Garner, Jennifer, 1972-; Hill, Jonah, 1983-; C. K., Louis; Tambor, Jeffrey, 1944-; Lowe, Rob; Flanagan, Fionnula, 1941-; Fey, Tina, 1970- (Distributed by Warner Home Video, 2010)
Mark is a desperate unemployed writer who lives in a world where everyone unfailingly tells the truth. People don't even know what fiction is. Every thought, no matter how humiliating or harsh, tumbles out unvarnished. Then one day, Mark becomes so desperate he concocts a lie. In a world where everyone is unfailingly honest, a lie is believed with total and absolute gullibility. Mark can get anything he wants. The one thing he truly wants is the love of a girl named Anna who happens to be the one person he can't bring himself to lie to.